Off farm employment among paddy farmers in the Muda and Kemasin Semarak granary areas, Malaysia - Ismaila, Sadiya Sami (2008)
Poverty is one of the most serious problems confronting paddy farmers worldwide, Malaysia inclusive. Off farm employment is an alternative strategy and has a potential to improve the income and well being of the paddy farmers. This study assessed the off farm employment decision among 500 paddy farmers in Muda Agricultural Development Authority and Kemasin Semerak granary areas. Specifically the study determined the relationship between the determinants of off farm and the off farm participation decision. It also describes the characteristics of respondents and their status in off farm employment. And it also tests hypotheses of relationships between off farm and individual, family and farm characteristics. Furthermore, it examined the income level of the farm households from paddy farming and off-farm employments and shows the effect of off farm employment to paddy farmers, using descriptive analysis, chi- square () analysis and logit regression methods. Cross tabulation were applied to identify the relationship between dependent variable (off farm employment) and independent variables (age, gender, education, dependents size, other income, farm size and type). Chi-square was used to test the null hypothesis, stating that “there is no relationship between off farm employment and individual, family and farm characteristics respectively”. To know the strength of the relationship between the variables that shows statistical significance with the dependant variable, Logit regression model was used. From the overall empirical analysis of the results, the variables that show highly statistically significant association with off farm employment are age of farmers, gender number of dependants other income and farm type. Evidently farm size and education were not significant factors affecting off farm participation decision as no significant association was observed between them and off farm participation.